Understanding the laundering of organized crime money - Levi, Mike (Crime and justice, 2020)
Four conditions influence the complexity of organized crime money laundering. First are diverse types of crime and forms in which proceeds are generated, including the type of payment, the visibility of crimes to victims or authorities, and the lapse before financial investigation occurs (if it does). Second, the amount of individual net profits causes differences between criminals who have no use for laundering, who self-launder, and who need assistance from third parties. Third are the offender’s goals and preferences in spending and investing crime proceeds. Investments are often close to home or country; some opt to wield power, but much is freely spent on a hedonistic lifestyle. Fourth, expected and actual levels of scrutiny and intervention of the anti–money laundering regime influence saving and reinvestment decisions and some arrests and confiscations, but there is no clear cause-and-effect relationship. The four conditions can intertwine in numerous ways. When conditions necessitate or stimulate more complex laundering schemes, this is reflected not only in techniques but also in social networks that emerge or are preconditions. Complex cases often depend on the assistance of professionals, outsiders to the criminal’s usual circle, who are hired to solve particular financial and jurisdictional bottlenecks.